Novel Technique for Secure Medical Image Transmission - Ellapalli, Anant Shankar; Varadarajan, S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The quest to develop cutting-edge security mechanisms is increasing due to digitalization, the development of the Internet, and the necessity of confidential communication in every industry governed by the Internet. Advanced declaration, computerized mark, and encryption are only a few of the methods employed to address these security concerns. Yet these approaches can't get you far in negotiations. To address these concerns this work proposes a hybrid model that utilizes both steganography and encryption to provide dual security to the data. Accordingly, to embed large quantities of data, Adaptively Scanned Wavelet Difference Reduction model is utilized to compress the secret image initially followed by ASCII-based encryption and embedding utilizing Lifting wavelet transform (LWT) coefficients. This work mainly concentrates on hiding the analyzed covid-19 chest X-rays utilizing the introduced hybrid model. To validate the proposed model, several experiments were conducted and obtained various image quality assessment metrics. From the relative analysis, it was evident that the proposal outperforms its peers.